Corporate Legal Liability for Environmental Damage (Case Study of Corporate Liability in Indonesia) - Edhei Sulistyo, Pujiyono, Nur Rohaeti (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Indonesia adopts environmental laws relatively oriented towards fines, although corporate participation in various laws regulating the environment is low. Therefore, it is necessary to develop the concept of responsibility. Corporations, especially in the event of environmental pollution or damage by the corporation. The purpose of this research is to see and identify the extent to which forms of responsibility for the composition of environmental damage, both in terms of punishment and compensation. This research was conducted using qualitative methods and normative juridical approaches. The results show that the application of the concept of Strict Liability to business actors accused of environmental crimes will impact investigating environmental crimes. The principle of Strict Liability is regulated explicitly in Law Number 32 of 2009 concerning Environmental Protection and Management. The principle of strict liability will make it easier for public prosecutors, that in the process of proof in court, public prosecutors do not need to prove mistakes in the form of deliberate acts or negligence on the part of the corporation that has committed a criminal act. The public prosecutor does not need to prove the existence of law enforcement or corporate motives for environmental crimes.